The first DNA-assisted record of Hemelytroblatta livida (Blattodea: Corydiidae) from Georgia with notes on Corydiinae species composition in the Caucasus - Armen Seropian; Eka Arsenashvili; Natalia Bulbulashvili; Lasha-Giorgi Japaridze; Aleqsandre Zukakishvili; Shota Japarashvili; Aleksi Memishishi; Levan Mumladze (Caucasiana, 2023)
The fossorial sand cockroach Hemelytroblatta livida (Brunner von Wattenwyl, 1865) is reported from Georgia for the first time, with a commentary on the species composition of the Corydiinae Saussure, 1864 subfamily in the Caucasus. Collection data, pictures of the male and female, and DNA barcodes are also provided. Furthermore, information on Polyphaga aegyptiaca (Linnaeus, 1758) is provided, along with images of the male, female, and juvenile.